PENGARUH PEMBERIAN FISIOTERAPI DADA TERHADAP KEBERSIHAN JALAN NAPAS PADA PASIEN ISPA DI DESA PUCUNG EROMOKO WONOGIRI - Ariasti, Dinar; Aminingsih, Sri; -, Endrawati (KOSALA : Jurnal Ilmu Kesehatan, 2014)
AbstractBackground: In the Indonesian case ARI (Acute Respiratory Infection) ranks first in the number of outpatients most. This shows morbidity due to ARI is still high. The government has planned to bring it down to 3 per 1,000 infants in 2010, however, the morbidity can be down depend on the number of risk factors, particularly those associated with the standard strategy of case management, immunizations, and risk factor modification. One of the management for the cleanliness of the airway in patients with ARI is chest physiotherapy. The purpose of this study was to determine the effect of chest physiotherapy on the cleanliness of the airway in patients with ARI in the Pucung village, Eromoko, Wonogiri. The subjects of this study were children Pucung villagers, Eromoko, Wonogiri aged under 10 years who suffered from ARI, amounting to 26 respondents. Sampling is done by accidental sampling technique is limited because the number of respondents. Data collected by observation using a pretest before giving chest physiotherapy and posttest after giving chest physiotherapy. The results of the pretest before giving chest physiotherapy is the number of respondents who clean airway hygiene there are 3 respondents (11.53%) and the number of respondents who did not clean her airway hygiene, there are 23 respondents (88, 47%). Posttest results after administration of chest physiotherapy is the number of respondents who clean airway hygiene, there are 18 respondents (69.23%) and the number of respondents who did not clean her airway hygiene there are 8 respondents (30.70%). Then the gathered data was analyzed by Paired t-test with p = 5% (0:05), so that the obtained p = 0.000 P <0.05. Based on the research results of Ho rejected and Ha accepted. The conclusion of this study is that there is the effect of chest physiotherapy on the cleanliness of the airway in patients with ARI.Keywords: Chest Physiotherapy, Health Airway, Acute Respiratory Infection